Elderly physical well being system - Oh, Yao Wen (Nanyang Technological University, 2022)
During the Covid-19 pandemic, many individuals' physical and mental well-being were affected, especially the elderly. As a large portion of the elderly in Singapore live alone, coupled with the Covid-19 restrictions, the elderly are isolated in their own homes, creating a decremental effect on their physical and mental health. Seniors find themselves at home more often as they are more vulnerable to Covid-19. This, unfortunately, leads to the elderly spending less time exercising and socialising and may cause their physical and psychological health to deteriorate. Hence, there is an urgent need for a sustainable solution that can improve the elderly well-being at home. As Singapore accelerates its digitalisation plans, initiatives such as "Seniors Go Digital" enable more elderly to have basic digital skills. This creates opportunities for developers to develop a system that allows elderlies to carry out simple exercises and entertain themselves at home. The Elderly Physical Well-Being System is designed to allow and encourage the elderly to work out and keep fit in their own home alone and improve their overall well-being. The system consists of two main components. The first component will be the Adafruit Feather nRF52840 Express. It is an all-in-one system that consists of multiple sensors and supports Bluetooth Low Energy. It collects orientation data that tracks the exercises. The second component is an Android tablet that will retrieve the elderly exercise data and incorporate it with a game running on the Android tablet.